2004
DOI: 10.1007/s00441-003-0849-3
|View full text |Cite
|
Sign up to set email alerts
|

Localization and expression of the glutamate transporter, excitatory amino acid transporter 4, within astrocytes of the rat retina

Abstract: Mechanisms for the removal of glutamate are vital for maintaining normal function of the retina. Five excitatory amino acid transporters have been characterized to date from neuronal tissue, all of which are expressed within the retina except excitatory amino acid transporter 4 (EAAT4). In this study we examined the expression and localization of the glutamate transporter EAAT4 in the rat retina using RT-PCR and immunocytochemistry. RT-PCR using rat EAAT4 specific primers revealed a prominent 296-bp product in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
8

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 24 publications
2
38
0
8
Order By: Relevance
“…We have recently shown that EAAT4 is expressed by astrocytes in the retina [14]. Figure 1c and d shows EAAT4 labelling in whole-mounted control and diabetic rat retinae 12 weeks post-diabetogenesis.…”
Section: Glutamate Transporter Expression In Müller Cells and Astrocymentioning
confidence: 87%
See 2 more Smart Citations
“…We have recently shown that EAAT4 is expressed by astrocytes in the retina [14]. Figure 1c and d shows EAAT4 labelling in whole-mounted control and diabetic rat retinae 12 weeks post-diabetogenesis.…”
Section: Glutamate Transporter Expression In Müller Cells and Astrocymentioning
confidence: 87%
“…Astrocytes are intricately linked with the vasculature and have processes within the nerve fibre and ganglion cell layers [12]. The function of astrocytes within the retina is not clearly defined, although they do express glutamate transporters such as GLAST and EAAT4 [13,14]. Highlighting the potential importance of these glutamate transporters in retinal pathology, studies have reported increased glutamate concentrations within the vitreous of patients with diabetes and in diabetic retinae [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mammalian retina expresses all the excitatory amino acid transporters, GLAST, GLT-1, EAAC1, EAAT4, and EAAT 5 (Seal and Amara, 1998;Pow, 2001a;Ward et al, 2004). Although it is known the transporters are expressed by different retinal cell types (Pow, 2001a), the relative contribution of the The primer design and PCR conditions were as described by Matsuo et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…EAAC1 (EAAT3) is present in neurons in the inner retina (Rauen et al, 1996;Schultz and Stell, 1996). EAAT4 has been reported in retinal astrocytes (Ward et al, 2004), while EAAT5 is localized to photoreceptors, bipolar cells, and possibly some Mü ller cells (Arriza et al, 1997;Eliasof et al, 1998a;Barnett and Pow, 2000).…”
Section: Introductionmentioning
confidence: 99%